A Multisource Approach to Assessing Child Maltreatment From Records, Caregivers, and Children. (February 2017) - Sierau, Susan; Brand, Tilman; Manly, Jody Todd; Schlesier-Michel, Andrea; Klein, Annette M.; Andreas, Anna; Garzón, Leonhard Quintero; Keil, Jan; Binser, Martin J.; von Klitzing, Kai; White, Lars O.
Practitioners and researchers alike face the challenge that different sources report inconsistent information regarding child maltreatment. The present study capitalizes on concordance and discordance between different sources and probes applicability of a multisource approach to data from three perspectives on maltreatment—Child Protection Services (CPS) records, caregivers, and children. The sample comprised 686 participants in early childhood (3- to 8-year-olds; n = 275) or late childhood/adolescence (9- to 16-year-olds; n = 411), 161 from two CPS sites and 525 from the community oversampled for psychosocial risk. We established three components within a factor-analytic approach: the shared variance between sources on presence of maltreatment (convergence), nonshared variance resulting from the child's own perspective, and the caregiver versus CPS perspective. The shared variance between sources was the strongest predictor of caregiver- and self-reported child symptoms. Child perspective and caregiver versus CPS perspective mainly added predictive strength of symptoms in late childhood/adolescence over and above convergence in the case of emotional maltreatment, lack of supervision, and physical abuse. By contrast, convergence almost fully accounted for child symptoms for failure to provide. Our results suggest consistent information from different sources reporting on maltreatment is, on average, the best indicator of child risk.